Identification of Robust Controller for 150hp 3 Phase Induction Motor - Sathishkumar, H.; Parthasarathy, S. S. (Asian Journal of Electrical Sciences, 2019)
In this paper, comparative performance analysis of Neural network controller and Neuro-fuzzy controller for 150hp (Horse power) three phase induction motor which is used in cable industry (Ravicab cables private limited) at Bidadi is presented. Proportional integral derivative (PID) controller based voltage frequency drive (VFD) is used here to control the speed of 150hp three phase induction motor which is used in cable drawing process. Since VFD used in this industry is affected by several disturbances, robust speed controller is to be interfaced with the three phase induction motor. In order to identify and interface the robust controller, this paper deals with problem of the currently existing cable industry with real time data. Moreover this paper proposes two proposed controller to solve this problem. Performances of these two proposed systems are explained with the help of Simulation and comparison chart. At the end robust controller for this cable industry will be identified.